Peripheral education of the immune system by the colonic microbiota - Kuhn, Kristine A. (2013)
There is growing interest in understanding the effects of host-microbial interactions on host physiologic processes. Much of the work in this arena is logically focused on the interaction at mucosal surfaces as this is a primary site of interaction. However, there is ample evidence to suggest that the effects of the microbiota have a much farther reach including the systemic immune system. While there are some similarities to effects at mucosal surfaces (i.e. reduced numbers of adaptive immune cells, diminished innate responses), there are some important differences that we highlight such as the response to immunogens and bacterial antigens. We propose that understanding the details of how specific components of the microbiota influence the systemic immune system likely will have significant impact on our understanding the pathophysiology of a variety of autoimmune diseases.